MASS MEDIA IN DISSEMINATING ENVIRONMENTAL AWARENESS - Singh Kushwaha, Vibha (International Journal of Research -GRANTHAALAYAH, 2015)
Developments in the field of science and technology while paving way for too many revolutions on the one hand had resulted in serious environmental problems on the other. At this juncture, the role of mass media becomes pertinent in spreading environmental awareness. The approach to entertainment- education can be a very promising one in creating environmental awareness via the usage of media such as, newspapers and magazines, radio, television and Internet.